Pengembangan Potensi Anak Melalui Islamic Youth Festival di Desa Menggare Slahung Ponorogo - Soraya, Siti; Shilvia Nurin Ni’mah; Bryan Hakim Sakti Pradana (Universitas Islam Negeri Raden Mas Said Surakarta, 2024)
Every individual is born with various potentials, and as they age, these potentials will develop according to their interests and talents. For these interests and talents to grow and develop, concrete efforts are needed to develop this potential. The approach used in this service activity follows the principles of Asset-Based Community Development (ABCD), which involves stages such as Inculturation, Discovery, Design, Define, and Reflection. The primary purpose of this community service activity is to stimulate talents and interests and instil the values ​​of ukhuwah Islamiyah in children in Menggare Village by holding the Islamic Youth Festival. This event involved 19 students and participants from various levels of education, from playgroup to elementary school, on 29 - 30 July 2023. The events at this festival included a series of competitions on the first day, leisure walks, and watching movies together on the second day. The competition involved colouring calligraphy, memorizing daily prayers, short letters, calling to prayer, and quizzes. The positive impact of this service program can be seen through the children's ability to recognize their talents and interests and the enthusiasm shown in showing these talents and interests through various competition activities.